2006
DOI: 10.1111/j.1525-1497.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

A matter of perspective

Abstract: Treatment preferences may be substantially influenced by a decision-making role. As certain roles appear to reinforce "big picture" thinking about difficult risk tradeoffs, physicians and patients should consider re-framing treatment decisions to gain new, and hopefully beneficial, perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(69 citation statements)
references
References 30 publications
15
53
0
1
Order By: Relevance
“…Although effect sizes for our findings were small (Cohen, 1988), they were consistent across the three experiments. These findings are also consistent with previous work examining imaginary economic judgments for the self (Horowitz & McConnell, 2002;Votinov et al, 2010) and others (Morewedge et al 2009;Zikmund-Fisher et al, 2006). Of interest, in two of our three experiments, we also found that participants valued objects owned by their close others more than objects they themselves owned.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although effect sizes for our findings were small (Cohen, 1988), they were consistent across the three experiments. These findings are also consistent with previous work examining imaginary economic judgments for the self (Horowitz & McConnell, 2002;Votinov et al, 2010) and others (Morewedge et al 2009;Zikmund-Fisher et al, 2006). Of interest, in two of our three experiments, we also found that participants valued objects owned by their close others more than objects they themselves owned.…”
Section: Discussionsupporting
confidence: 92%
“…However, this increased level of risk aversion may occur only for low-impact decisions. In fact, the self-other difference in risk aversion may be reversed for high-impact decisions such as those involving health (Fernandez-Duque & Wifall, 2007;Stone, Choi, de Bruin, & Mandel, 2013;Zikmund-Fisher, Sarr, Fagerlin, & Ubel, 2006).…”
Section: Decision Making For Othersmentioning
confidence: 97%
“…A future direction would be to investigate how medical decisions are and should be negotiated within families, for example, to minimize the negative emotional impact the choice and the choice outcomes have on all family members. This line of research would tap not only into the literature on shared decision making about health [30]–[32], but also into the more recent studies reporting systematic differences between the treatment choice one recommends for another person vs. makes for oneself (see [23], [33]). How can we better involve minors and their families in the process of making medical decisions?…”
Section: Discussionmentioning
confidence: 99%
“…Research in the broader field of decision-making indicates that individuals make systematically different choices when asked to advise or decide for another than to decide for themselves (Beisswanger et al, 2003;Zikmund-Fisher et al, 2006), including displaying fewer cognitive biases when deciding for others (Ubel, Angott, & Zikmund-Fisher, 2011) and placing greater weight on the most important factors in the decision (Kray & Gonzalez, 1999).…”
mentioning
confidence: 99%